POSSIBILITIES FOR ENERGY EXPLOITATION OF LANDFILL GAS FROM OLD MUNICIPAL SOLID WASTE LANDFILLS IN SLOVENIA - Kortnik, Jože (Journal of Energy Technology, 2024)
In Slovenia, landfill gas is presently exploited at only fifth municipal solid waste (MSW) landfills. Practice has shown that the installation of facilities for the exploitation of landfill gas for producing electrical energy is cost-efficient only at those landfills that collect over 60,000 tons or m³ of waste annually. A quick calculation for Slovenia shows that the use of landfill gas in gas-operated generators could be done at 17, not merely 10 MSW landfills (and it is presently done at only 4). In this way, Slovenia could quickly achieve the prescribed 21% of electrical energy from renewable energy sources by the year 2020 (which presently ranges between 18% and 19%). Although there is a possibility of cost-efficient exploitation of landfill gas even at smaller MSW landfills, which receive from 20,000 to 60,000 tons of municipal solid waste per year, in the case of smaller gas-operated generators (143 kWe) that require more demanding maintenance and the need to construct an additional system for active landfill degassing, suchinvestments may be at the limit of profitability. This paper presents potentially generated quantities of landfill gas and assesses the possibilities for energy exploitation of landfill gas from the already closed old non-hazardous waste deposits at Leskovec and Bukovzlak, using the LandGEM software package.